Profile of Collaborative Problem Solving among XI Grade Students in Solving Financial Mathematics Problems - Hikmah, Nur Hidayatul; Siswono, Tatag Yuli Eko; Zahri, Mohammad (Journal of Mathematical Pedagogy (JoMP), 2021)
The aim of this research is to describe CPS profile of XI grade students in solving financial mathematics problem. The subject of this research was three pairs of XI grade students which: a pair student consisting of medium-high ability students, a pair student who are both had high ability and a pair student consisting of low-medium ability students. The result showed that a pair student who are both had high ability were able to answer all the question correctly. A pair student consisting of medium-high ability students almost answered all the questions correctly and a pair student consisting of low and medium ability students were unable to answer all the questions correctly. A pair student who are both had high ability and a pair student consisting of medium-high ability students able to design and do problem solving activities well. They also able to work well together when solving the problems. However, a pair student consisting of low-medium ability students unable to design and do the problem solving activities well. They also unable to work well together when solving the problem and tend to work individually. It can be said that based on collaborative problem solving indicators and problem solving result obtained, collaborative problem solving in a pair student who are both had high ability much better than othes.